Teachers' Challenges During the Transition from the 2013 Curriculum to the Independent Curriculum in Elementary Schools (Lembaran Ilmu Kependidikan, 2025)
The curriculum is a system encompassing structured objectives, learning materials, and teaching methods to guide education toward optimal outcomes. As a flexible element, it evolves to meet societal needs. The purpose of this study is to examine the obstacles encountered during the shift from the 2013 Curriculum to the Independent Curriculum, evaluate teachers' readiness to implement it, and provide recommendations for enhancing its application in elementary schools. Adopting a qualitative descriptive method with a case study design, data was gathered through observations, interviews, and document analysis, with triangulation employed to ensure the accuracy of the findings. Data analysis was conducted using Miles and Huberman’s framework, which includes steps of data reduction, data presentation, and drawing conclusions. The research revealed considerable obstacles in the implementation of the Independent Curriculum, especially for senior educators who struggle with issues related to digital literacy and adapting to new technologies. Other obstacles include insufficient training, limited socialization, and inadequate resources such as teaching materials and technological infrastructure. While teachers possess a foundational understanding of the Independent Curriculum, their preparedness for its full implementation, particularly at SD Negeri 2 Jatisari, remains inadequate. Efforts to address these challenges include teacher and principal training and the use of digital platforms like the Independent Teaching Platform. These initiatives aim to improve understanding and practical application, ensuring smoother curriculum implementation in the future.